Agricultural culture among secondary school students in rural Peru (GnosisWisdom, 2022)
The research problem is centered on the lack of agricultural education proposals for a sustainable life project in rural Peruvian students at the secondary level. The present study has the purpose of developing a documentary diagnosis on the situation of agricultural education of students in rural areas, at the secondary level, considering as bases of the model the didactic, psycho-pedagogical and gnoseological characterization that allows the systematization of a proposal, exercising for it a bibliographic scrutiny of the state of the art in its heuristic and hermeneutic phases with the historiographic analysis on the teaching-learning of students according to the secondary level in rural areas. The present work is descriptive and propositive, so it is based on an urgent requirement within Peruvian institutions. Theoretical aspects will be contributed as support for other studies concerning the education sector. Within the framework of a practical significance is the preparation of an agricultural education offer for the improvement of the sustainable life project. It is concluded that the curricula offered by the educational institutions do not cover the training deficiencies of the students in their agricultural activities.
Keywords: sustainable development; agricultural education; life project